EFFECT OF E-SERVICE QUALITY, PRODUCT COMPLETENESS AND PROMOTION ON CONSUMER REPURCHASE INTEREST (CASE STUDY MATAHARI.COM) - Dadan Rusdiana (Jurnal Ekonomi, 2022)
The population in this research is a consumer who has visited the website and application on Matahari.com in Bandung city. The sampling technique uses Structural Equation Model (SEM) analysis method with the number of samples as much as 140 people. The data analysis technique used is multiple regression. The results showed that: (1) There is a positive influence of e-service quality against the interest of repurchase of consumers (Matahari.com cases study), proven t-count value of 2.120, (2) there is a positive influence of product completeness to Consumer's re-purchase interest (Matahari.com cases study), subtantion by the t-count value of 2.201, (3) there is a positive influence on promotion of consumer repurchase interest (Matahari.com cases study). Subtantion from the t-count value of 4.059 and (4) there is the influence of e-service quality, completeness of products and the promotion together against the interest of the re-purchase of consumers (Matahari.com cases study), evidenced by the value F count of 13.841.The results showed that e-service quality, completeness of products, promotion and interest of the repurchase of consumers on Matahari.com have the value that goes to the category "Satisfied"